Billroth‐I vs Roux‐en‐Y after distal gastrectomy: A comparison of long‐term nutritional status and survival rates from a large‐scale multicenter cohort study. Issue 2 (4th February 2020) - Kinoshita, Takahiro; Honda, Michitaka; Matsuki, Atsushi; Enomoto, Naoki; Aizawa, Masaki; Nunobe, Souya; Yabusaki, Hiroshi; Abe, Takayuki; Hiki, Naoki
Abstract: Background: The optimal standard reconstruction procedure after distal gastrectomy is controversial. No large‐scale persuasive clinical studies from long‐term perspectives on this topic have yet been conducted. Study design: This retrospective multicenter study analyzed a database of 2510 consecutive patients with clinical stage I gastric cancer who underwent distal gastrectomy followed by Billroth‐I (B‐I) or Roux‐en‐Y (R‐Y) anastomosis from 2006 to 2012. After adjusting for 30 potential confounding factors using propensity score matching, we compared the body weight loss and other nutritional status for 5 years as primary outcomes between the two groups. We also investigated surgical outcomes, endoscopic findings, and long‐term survival rates as secondary outcomes. Results: After matching the inclusion criteria, 940 patients (470 in each group) were enrolled. There was no marked difference in the body weight loss and other nutritional indicators. The incidence of grade ≥3 postoperative complications (Clavien‐Dindo classification) or the incidence of gallstone formation was not markedly different between the two groups. The postoperative hospital stay after surgery was significantly longer, and the readmission rate was significantly higher in the R‐Y group than in the B‐I group. An endoscopic examination revealed no trends regarding the incidence and severity of gastritis or residual food in the remnant stomach. The 5‐year overall survival rate was 92.6% in the B‐I group and 91.8% in the R‐Y group, with no significant difference ( P  = .379, log‐rank test). Conclusions: Roux‐en‐Y reconstruction may be nearly equal to Billroth‐I with regard to the long‐term nutritional perspectives. Abstract : This retrospective multicenter study analyzed a database of 2510 consecutive patients with clinical stage I gastric cancer who underwent distal gastrectomy followed by Billroth‐I (B‐I) or Roux‐en‐Y (R‐Y) anastomosis. There was no marked difference in the body weight loss and other nutritional indicators. Roux‐en‐Y reconstruction may be nearly equal to Billroth‐I with regard to long‐term nutritional perspectives.